1989
DOI: 10.1126/science.2467382
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Inhibits NMDA-Activated Ion Current in Hippocampal Neurons

Abstract: The ion current induced by the glutamate receptor agonist N-methyl-D-aspartate (NMDA) in voltage-clamped hippocampal neurons was inhibited by ethanol (EtOH). Inhibition increased in a concentration-dependent manner over the range 5 to 50 mM, a range that also produces intoxication. The amplitude of the NMDA-activated current was reduced 61 percent by 50 mM EtOH; in contrast, this concentration of EtOH reduced the amplitude of current activated by the glutamate receptor agonists kainate and quisqualate by only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
667
9
7

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,341 publications
(742 citation statements)
references
References 36 publications
45
667
9
7
Order By: Relevance
“…As previously observed in the hippocampus (Weiner et al, 1999), acute ethanol inhibited synaptically evoked postsynaptic amygdalar KA EPSCs more potently than either AMPA EPSCs, which were not affected by even the highest concentration of ethanol tested (80 mM), or NMDA receptor-mediated synaptic responses, which were only significantly inhibited at this highest concentration. These findings agree with other reports of postsynaptic inhibition of NMDA receptors by acute ethanol in isolated cells of the BLA (Floyd et al, 2003), in the hippocampus (Lovinger et al, 1989), central nucleus of the amygdala (Roberto et al, 2004) and the ventral bed nucleus of the stria terminalis (Kash et al, 2007). Acute ethanol has been shown to have no effect on AMPA receptors in the hippocampus with a small, 12% inhibition on composite AMPA and KA-R currents in cerebellar granular cells (Valenzuela et al, 1998).…”
Section: Acute Ethanol Inhibits Ka Epscs Via a Postsynaptic Mechanismsupporting
confidence: 92%
“…As previously observed in the hippocampus (Weiner et al, 1999), acute ethanol inhibited synaptically evoked postsynaptic amygdalar KA EPSCs more potently than either AMPA EPSCs, which were not affected by even the highest concentration of ethanol tested (80 mM), or NMDA receptor-mediated synaptic responses, which were only significantly inhibited at this highest concentration. These findings agree with other reports of postsynaptic inhibition of NMDA receptors by acute ethanol in isolated cells of the BLA (Floyd et al, 2003), in the hippocampus (Lovinger et al, 1989), central nucleus of the amygdala (Roberto et al, 2004) and the ventral bed nucleus of the stria terminalis (Kash et al, 2007). Acute ethanol has been shown to have no effect on AMPA receptors in the hippocampus with a small, 12% inhibition on composite AMPA and KA-R currents in cerebellar granular cells (Valenzuela et al, 1998).…”
Section: Acute Ethanol Inhibits Ka Epscs Via a Postsynaptic Mechanismsupporting
confidence: 92%
“…Another potential problem is that ethanol is known to affect several neurotransmitter systems including GABA (Roberto et al, 2003), glutamate (Lovinger et al, 1989), neuroactive steroids (Sanna et al, 2004), and a variety of neuropeptides including opioids (de Gortari et al, 2000) and CRF (Nie et al, 2004). Therefore, even if opioid receptors modulate GABA A receptor function in the amygdala, the ability of ethanol to affect other neurotransmitter and neuromodulatory systems may be sufficient to circumvent any opioid receptor effects on GABA A receptor function localized selectively within the CeA or BLA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support this hypothesis and clearly show that alkylbenzenes and TCE can signi®cantly inhibit the function of this ion channel. NMDA receptors thus appear to be inhibited by several classes of compounds that show abuse liability including phencyclidine, nitrous oxide, ethanol, and now abused volatile solvents (Lodge & Johnson, 1990;Jevtovic-Todorovic et al, 1998;Lovinger et al, 1989;Kuner et al, 1993;Masood et al, 1994, Mirshahi & Woodward, 1995. While some of these compounds may be relatively selective for NMDA receptors (phencyclidine, nitrous oxide), others like ethanol appear to be e ective at a number of important ligand-gated ion channels including those activated by GABA and glycine.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the idea that inhalants may share a common mechanism of action with other abused depressant drugs such as ethanol. One of the best-studied targets of depressant drugs is the glutamate family of ionotropic receptors (Lovinger et al, 1989;Grant & Lovinger, 1995). Using the oocyte expression system, we have previously reported that toluene dosedependently inhibited NMDA-mediated currents at micromolar concentrations.…”
Section: Introductionmentioning
confidence: 99%